THE EFFECTS OF THE ZINC SUPPLEMENTATION AND WEIGHT TRAININGS ON THE TESTOSTERONE LEVELS - Cinar, V.; Talaghir, L. G.; Akbulut, T.; Turgut, M.; Sarikaya, M. (South Ural State Univ, Scientific Research Dept, 2017)
Aim. The purpose of this study, it has been aimed to examine the effects of zinc supplementation applied with weight trainings on the testosterone levels in sedentary individuals and athletes. Materials and Methods. As methods of work it was selected 40 male, 20 sedentary male and 20 male who do physical exercises regularly, participated in the study. The participants are divided equally into 4 groups. The groups are constituted in that way: 1st Group: Control Group (S), 2nd Group: Sedentary Group which is supplied with Zinc (Z), 3rd Group: Training Group which is supplied with Zinc (ZT) and 4th Group: Athletes' Group who performs the weight training (T). The total testosterone and free testosterone values of the participants were measured from the blood samples which were drawn from the participants at the beginning and at the end of the 6-week training period. Results. Like results, has been asserted that the total and free testosterone values of the groups which are supplied with Zinc and perform weight training have increased depending on training and supplementation. Conclusion. In conclusion consequently it has been determined that 6-week zinc supplementation and weight training increase the testosterone levels. Accordingly, it may be said that this implementation contributes to the performance.
Keywords: exercise; zinc supplementation; testosterone